2022
DOI: 10.3390/ijms23115945
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms during Osteogenic Differentiation in Human Dental Follicle Cells

Abstract: Human dental follicle cells (DFCs) as periodontal progenitor cells are used for studies and research in regenerative medicine and not only in dentistry. Even if innovative regenerative therapies in medicine are often considered the main research area for dental stem cells, these cells are also very useful in basic research and here, for example, for the elucidation of molecular processes in the differentiation into mineralizing cells. This article summarizes the molecular mechanisms driving osteogenic differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 129 publications
0
11
0
Order By: Relevance
“…Osteoblasts are differentiated from BMSCs and exhibit critical roles in bone formation. Osteogenic differentiation is complex and orchestrated by various signaling pathways, such as Wnt/β-catenin, TGFβ/BMP, MAPK, and Notch signaling pathways [ 64 ]. Early osteogenic biomarkers, such as ALP, RUNX2, and SP7, and late biomarkers, such as OPN and OCN, have been used to evaluate the biological effects of potential candidates [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts are differentiated from BMSCs and exhibit critical roles in bone formation. Osteogenic differentiation is complex and orchestrated by various signaling pathways, such as Wnt/β-catenin, TGFβ/BMP, MAPK, and Notch signaling pathways [ 64 ]. Early osteogenic biomarkers, such as ALP, RUNX2, and SP7, and late biomarkers, such as OPN and OCN, have been used to evaluate the biological effects of potential candidates [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers found that microRNA-935-modified BMSCs promoted the proliferation and differentiation of osteoblasts in osteoporotic rats through the secretion of extracellular vesicles carrying miR-935 targeting STAT1 ( Morsczeck, 2022 ). In terms of long noncoding RNAs (lncRNAs), knocking out TUG1 inhibited the growth, proliferation, and invasion of OSCC cells by targeting the Wnt/β-catenin signaling pathway and inducing apoptosis of OSCC cells.…”
Section: Role Of Cell Optimization In Oral Diseasesmentioning
confidence: 99%
“…25 During osteogenic differentiation, DFCs maintain a consistent expression of osteogenic transcription factors, enhanced mineral deposition, and an upregulation of osteogenic markers. 26,27 DFCs aid periodontal repair through osteopontin (OPN)-mediated processes in inflammation. 28 They also restore regenerative capabilities to periodontal ligament stem cells under inflammatory conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Derived from the dental follicle, dental follicle stem cells (DFCs) possess pluripotency, capable of differentiating into periodontal ligament cells, osteoblasts, and odontoblasts. Comparable immunomodulatory and osteogenic properties observed in both freshly isolated and cryopreserved DFCs suggest robust cellular resilience . During osteogenic differentiation, DFCs maintain a consistent expression of osteogenic transcription factors, enhanced mineral deposition, and an upregulation of osteogenic markers. , DFCs aid periodontal repair through osteopontin (OPN)-mediated processes in inflammation . They also restore regenerative capabilities to periodontal ligament stem cells under inflammatory conditions .…”
Section: Introductionmentioning
confidence: 99%